The Starry Deer Caiman and Structure 44 at Yaxchilan, Chiapas, Mexico - Iwaniszewski, Stanislaw; Galindo Trejo, Jesús (Journal of Skyscape Archaeology, 2016)
This paper analyses the meaning of astronomical alignments of Structure 44 from Yaxchilan, Mexico. The lack of direct solar referents calls for a more integrative approach in which archaeoastronomy is supplemented by the research fields of archaeology, epigraphy and iconography. The designation of Structure 44 as an otoot (dwelling, house) building allows us to conceptualize it as a type of animate entity which is linked with the representation of the figure of the Starry Deer Caiman, one of the Maya Milky Way constellations.